2021
DOI: 10.1177/23259671211038992
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of UCL Repair Using Suspensory Fixation Versus UCL Reconstruction

Abstract: Background: Medial ulnar collateral ligament (mUCL) repair is growing in popularity as a treatment for younger athletes with mUCL tears. One of the most recent techniques utilizes a collagen-coated suture tape to augment the repair. The most popular repair technique uses a screw for proximal fixation in the humerus. We present an alternative technique that uses suspensory fixation in the proximal humerus. Purpose: To biomechanically compare elbow valgus stability and load to failure of a novel alternative repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Six biomechanical studies were identified from the literature. 7 , 9 , 19 , 27 , 31 , 43 In total, there were 106 cadaveric elbows, of which 53 were treated with ulnar collateral ligament (UCL) internal brace (IB) repair and 53 with UCL reconstruction. The mean age of the specimens was 63.7 years (range, 44.7-73.2 years), with 57.8% of the specimens being from men.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six biomechanical studies were identified from the literature. 7 , 9 , 19 , 27 , 31 , 43 In total, there were 106 cadaveric elbows, of which 53 were treated with ulnar collateral ligament (UCL) internal brace (IB) repair and 53 with UCL reconstruction. The mean age of the specimens was 63.7 years (range, 44.7-73.2 years), with 57.8% of the specimens being from men.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies had similar anchor and fixation placement for the FiberTape Internal Brace (Arthrex). 9 , 19 , 27 , 31 Of the remaining 2 studies, 1 had additional anchors incorporating SutureTape (Arthrex) in the sublime tubercle for posterior band augmentation. 43 The final study incorporated a novel suspensory fixation in the medial epicondyle for suture tape augmentation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Frank Jobe first described the successful reconstruction of the UCL in 1986, allowing athletes to return to their pre-injury level of the sport [19,20]. Since then, a variety of ulnar collateral ligament reconstruction (UCLR) techniques have been described, including methods that use both allograft and autograft tendons [12,22,23].…”
Section: Introductionmentioning
confidence: 99%